Defending Ireland : the Irish state and its enemies since 1922 - O'Halpin, Eunan (Oxford University Press, 2000)
This fascinating and original book is the first to analyse the evolution of internal security policy and external defence policy in Ireland from independence to the present day. Professor O'Halpin examines the very limited concept of external defence understood by the first generation of Irish leaders, going on to chart the state's repeated struggles with the IRA and with other perceived internal and external threats to stability. He explores the state's defence and security relations with Britain and the United States and, drawing extensively on newly released records, he deals authoritatively with problems of subversion, espionage, counterintelligence and codebreaking during the Second World War. In conclusion, the book analyses significant post-Second World War developments, including anti-communist co-operation with Western powers, the emergence of UN service as a key element of Irish foreign and defence policy, the state's response to the Northern Ireland crisis since 1969, and Ireland's difficulties in addressing the collective security dilemmas facing the European Union in the post-Cold War era.; It is essential reading for anyone wishing to understand the development of independent Ireland since 1922.